Animated Cinema as an Educational Medium :Towards a Audio-visual Pedagogy in Art Education (The International Journal of Educational Sciences and Arts, 2025)
This article investigates the role of animated cinema in art education, starting from a central problematic: how can an artistic and narrative audio-visual product be transformed into a didactic tool capable of balancing aesthetic enjoyment with pedagogical value? Building on this question, the study seeks to highlight the educational potential of animated cinema in renewing classroom practice, fostering visual literacy and critical thinking, and engaging learners as active participants in meaning-making rather than passive recipients. It further aims to show how this medium can serve as a pedagogical entry point for art education by integrating both cognitive and affective dimensions of learning.Methodologically, the research adopts a synthetic review of academic literature published between 2000 and 2025 in the fields of education, art, and aesthetics, combined with critical analysis that reconstructs previous findings into a unified theoretical framework. This theoretical perspective is reinforced by a case study of The Little Prince (2015), directed by Mark Osborne, which provides a concrete example of how narrative structure, visual language, and animation techniques can reshape the relationship between literature, art, and education.The study concludes that animated cinema should not be reduced to a supplementary teaching aid but recognized as a space of aesthetic and cognitive interaction that fosters interpretation, dialogue, and reflective learning. Its effective use, however, requires renewed pedagogical awareness capable of balancing artistic depth with educational functionality. Such an approach opens new perspectives for rethinking the strategic role of art education in contemporary schooling and its capacity to bridge creativity, knowledge, and values.
Keywords: Art Education; Animated Cinema; Pedagogy; Learner; Aesthetic Substitution; Audio-Visual Reception